THE EFFECT OF TRANSFORMATIONAL, TRANSACTIONAL, AND DIGITAL LEADERSHIP ON EMPLOYEE PERFORMANCE IN THE NEW NORMAL ERA (STUDY ON EMPLOYEES OF ANNA MEDIKA MADURA RSU) - Eka Suci Daniyanti; Enggal Sari Maduratna; Nailufar Firdaus (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: Leadership style is employee oriented and improves performance as well as builds a connection with each other trust, value, and respect. Leadership style is a technique used by a leader with destination control over other people's actions this interpreted that successful organization in communication among tops and bottoms is also determined by style leadership. Objectives: Study this measure of influence style leadership transformational, transactional are digital towards performance employees at RSU Anna Medika Madura in the new normal era.Methods: Study this is study quantitative with SPSS 25 program for windows. The population used as many as 65 respondents. Method analysis in a study is analysis regression multiple.Results: Research Results show that variable style leadership transformational (X1) no take effect by significant to performance employee with value (X1) = 0.173 > 0.05, style leadership transactional (X2) effect by significant to performance employee with value (X2) = 0.000 < 0.05, variable style digital leadership (X3) influential by significant to performance employee with value (X3) = 0.000 < 0.05.Conclusion: Leadership style transactional and digital effect significant to performance employees in the new normal era at RSU Anna Medika Madura. The new normal era coincides with digital transformation, and here the role of a capable leader to face digital change is very holding role important, think this is related to the enhanced performance of employees.